Recognition of psychogenic non-epileptic seizures: a curable neurophobia?. Issue 2 (28th July 2012) - O'Sullivan, Sean S; Redwood, Rebecca I; Hunt, David; McMahon, Elaine M; O'Sullivan, Suzanne
Abstract : Background: Diagnosing psychogenic non-epileptic seizures (PNES) remains challenging. The majority of 'PNES status' cases are likely to be seen in the emergency department or similar non-specialised units, where patients are initially assessed and managed by physicians of varying expertise in neurology. Methods: 216 participants including medical students and doctors of all grades from a wide range of medical disciplines were shown video recordings of six patients with PNES and six other patients with convulsive epileptic seizures (ES). Participants were asked to choose between PNES and ES as a diagnosis and to rate their confidence in each diagnosis, both before and after a 15-minute teaching presentation on PNES and ES. Results: Pre-teaching sensitivity for diagnosing PNES was 0.77, specificity 0.55. The positive predictive value (PPV) of diagnosing PNES was 0.63, and was 0.7 for ES. Diagnostic accuracy increased with increasing clinical grades (p=0.022), as did clinical confidence (p<0.0005). Clinical accuracy and clinical confidence increased post-teaching (p<0.0005). Sensitivity for diagnosing PNES post-teaching improved to 0.88, specificity to 0.67. The PPV of diagnosing PNES increased to 0.72, and to 0.84 for ES. Conclusions: Diagnosing PNES can be improved by clinical experience in neurology and focussed teaching interventions.